Calixarenes and Beyond - Neri, Placido; Sessler, Jonathan L.; Wang, Mei-Xiang (Springer International Publishing : Imprint: Springer, 2016)
Contributions featuring the chemistry and applications of a family of macrocyclic compounds collectively known as 'calixarenes' are presented in this edited volume. The arsenal of structures based on calixarenes provides tools which are effective in numerous areas of supramolecular chemistry. The Editors have compiled a timely volume which contains up to date, high calibre contributions from a large number of international authors. A broad perspective on the progress and future of calixarene chemistry is presented. Aimed at students and researchers active in Supramolecular Chemistry.